Clinical Practice and Safety of Endoscopic Balloon Dilation for Crohn’s Disease–Related Strictures: A Nationwide Claim Database Analysis in Japan - Rintaro Moroi; Kunio Tarasawa; Hiroshi Nagai; Yusuke Shimoyama; Takeo Naito; Hisashi Shiga; Shin Hamada; Yoichi Kakuta; Kiyohide Fushimi; Kenji Fujimori; Yoshitaka Kinouchi; Atsushi Masamune (Gastroenterology Research and Practice)
Conclusion: Our findings support the safe and effective use of EBD for both ileal and colonic strictures associated with CD. The clinical practice and safety outcomes of EBD for CD-related strictures were comparable to those for strictures stemming from other etiologies.